Membangun Human Capital: Strategi Peningkatan Pelayanan di Pasar Tradisional Ho Chi Minh Vietnam - Fadli, Uus Mohammad Darul; Tuhagana, Aji; Faddila, Syifa Pramudhita; Faddila, Hafsari Prabhamanik (Lumbung Pare Cendekia, 2025)
Traditional markets in Ho Chi Minh City face significant challenges in improving customer service quality, especially for foreign tourists. This community service program aims to build human resources for traditional market traders through customer service skills training and the application of digital technology. The activities focused on four main markets: Ben Thanh, Binh Tay, Tan Dinh, and An Dong, each of which has its own characteristics and challenges. The service methodology used a participatory approach. The training results showed improvements in service quality, tourists' cultural understanding, and the use of digital technology such as cashless payments and bold marketing. This article provides strategic recommendations for ending traditional markets as competitive cultural tourism destinations.